A time with e-Natureza (e-Nature): a model of nature-based health interventions as a complex adaptive system - Leão, Eliseth Ribeiro; Hingst-Zaher, Erika; Savieto, Roberta Maria; Patricio, Karina Pavão; de Oliveira, Leticia Bernardes; Catissi, Giulia; Lima, Luciano Moreira; Borba, Gustavo Benvenutti; Bomfim, Sabrina Bortolossi; de Abreu, Floriana Bertini (Frontiers in Psychology, 2023)
Abstract Discussions surrounding the positive impacts of nature on human health and strategies to enhance our connection with the natural world have been ongoing. However, a limited number of theoretical models are available to guide research and practice in this area. Therefore, there is a pressing need for a systematic framework that outlines clear steps for conducting research implementing nature-based interventions. In this study, we investigate the relationship between health and nature through the lens of Complex Adaptive Systems. This approach involves examining the dynamic interactions between multiple interconnected elements to understand the complex emergent behaviors that arise from such relationships. Our model is designed to support nature-based interventions, considering the essential interdependence between humans and nature. This perspective aims to improve both human health and biodiversity conservation in a mutually beneficial manner. The underlying interactions that drive nature-based health interventions are thoroughly explored, leading us to propose a novel intervention model named "A time with e-Natureza" (e-Nature). This model encompasses four types of experiences, drawing from scientific literature and insights from authors engaged in an interdisciplinary research group: 1) Aesthetic and emotional experience; 2) Multisensory integration experience; 3) Knowledge experience; and 4) Engagement experience. Each experience within the model targets affective, cognitive, and behavioral aspects, with a specific focus on fostering a deeper connection with nature. Distinct activities are incorporated within each experience to promote successful outcomes. The model is grounded in existing theories that address the human-nature relationship and is informed by Nursing theories that support health promotion interventions. By presenting this new model, our aim is to contribute to the effective implementation of nature-based interventions that not only enhance human well-being but also support the conservation of nature. This integrated approach recognizes the mutual benefits of human-nature interaction and offers valuable insights for future research and practical applications in the fields of nature and health.